What the Book Arts Can Teach Us About Sacred Texts: The Aesthetic Dimension of Scripture. Issue 1 (3rd July 2017) - Plate, S. Brent
Abstract : Religion and art became separated in the modern age, or so the secularized story goes. But looking at a history of books, including their artistic creation, we find interesting ongoing parallels occurring between religious and artistic texts. Illustrations and scripts, bindings and papers, printmaking and performance, all serve artistic and religious ends. The artistic and the religious are tied together, ultimately, by appealing to the senses, bringing texts and reading into the realm of the aesthetic (Gk. aesthetikos: pertaining to sense perception). Books are powerful and enjoyable as well as dangerous and condemned, because they are felt, seen, tasted, heard, and touched. By looking at contemporary "book arts" and noting their sensual affects, we can understand "sacred texts" in better ways. Ultimately we find modern secular arts are not so far from religious experiences. Examples come from modern book artists such as John Latham, Brian Dettmer, Luigi Serafini, Meg Hitchcock, and Guy Laramée.